Can short duration visual cues influence students’ reasoning and eye movements in physics problems? - Madsen, Adrian M.; Rouinfar, Amy; Larson, Adam M.; Loschky, Lester C.; Rebello, N. Sanjay (My University, 2013)
We investigate the effects of visual cueing on students’ eye movements and reasoning on introductory physics problems with diagrams. Participants in our study were randomly assigned to either the cued or noncued conditions, which differed by whether the participants saw conceptual physics problems overlaid with dynamic visual cues. Students in the cued condition were shown an initial problem, and if they answered that incorrectly, they were shown a series of problems each with selection and integration cues overlaid on the problem diagrams. Students in the noncued condition were also provided a series of problems, but without any visual cues. We found that significantly more participants in the cued condition answered the problems overlaid with visual cues correctly on one of the four problem sets used and a subsequent uncued problem (the transfer problem) on a different problem set. We also found that those in the cued condition spent significantly less time looking at “novicelike” areas of the diagram in the transfer problem on three of the four problem sets and significantly more time looking at the “expertlike” areas of the diagram in the transfer problem on one problem set. Thus, the use of visual cues to influence reasoning and visual attention in physics problems is promising.
Keywords: Visual cueing; Physics education; Visual attention; VIsual cues